Generalized analysis of harmonic distortion in the D-TCSC - E Silva, Luciano S. C (2015)
The objective of this work is to present a generalized analysis of power quality of the Thyristor Controlled Series Compensator for electrical distribution systems application (D-TCSC). The studies include normalized graphics that indicate the harmonic behavior and the possibilities of parallel resonance of D-TCSC. The main simulation results show the improvement of the voltage load and confirm the behavior of the normalized graphics that are presented in comparative Tables.